2003
DOI: 10.1016/s0304-3959(02)00420-7
|View full text |Cite
|
Sign up to set email alerts
|

Development of motor system dysfunction following whiplash injury

Abstract: Dysfunction in the motor system is a feature of persistent whiplash associated disorders. Little is known about motor dysfunction in the early stages following injury and of its progress in those persons who recover and those who develop persistent symptoms. This study measured prospectively, motor system function (cervical range of movement (ROM), joint position error (JPE) and activity of the superficial neck flexors (EMG) during a test of cranio-cervical flexion) as well as a measure of fear of re-injury (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
240
2
12

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 313 publications
(264 citation statements)
references
References 31 publications
10
240
2
12
Order By: Relevance
“…1 Half of all those exposed to a MVC will never fully recover but have milder symptoms, 2 and 25% (~ 1 million) are expected to present with a complex clinical picture including severe-pain-related disability, 3 muscle degeneration, 4,5 sensory and motor disturbances, 6 muscle weakness, 7 and psychological distress. 6 A number of psychosocial factors (e.g., coping, expectations, anxiety and depression) have been identified as being associated with poor functional recovery.…”
Section: Introductionmentioning
confidence: 99%
“…1 Half of all those exposed to a MVC will never fully recover but have milder symptoms, 2 and 25% (~ 1 million) are expected to present with a complex clinical picture including severe-pain-related disability, 3 muscle degeneration, 4,5 sensory and motor disturbances, 6 muscle weakness, 7 and psychological distress. 6 A number of psychosocial factors (e.g., coping, expectations, anxiety and depression) have been identified as being associated with poor functional recovery.…”
Section: Introductionmentioning
confidence: 99%
“…The neck muscles surrounding the cervical spine and the deep neck muscle layers play an important role in maintaining a stable base for the postural control of the neck (Mayoux-Benhamou et al 1994, Panjabi 1992. Impaired ventral neck muscle function has been reported in chronic neck pain (Falla et al 2004, Falla et al 2011) and WAD (Cagnie et al 2010, Elliott et al 2010, Peterson et al 2015a, Sterling et al 2003, but the function of the neck extensor muscles in WAD are not as well studied. Elliott et al (2008a) demonstrated fatty infiltrate in the extensor muscle in WAD using magnetic resonance imaging (MRI).…”
Section: Introductionmentioning
confidence: 99%
“…From this review we identified evidence of the following dysfunction,: thoracic spine pain in acute/sub-acute/chronic WAD ranging from minor injuries to more severe (WADIII) presentations [11,14,17,32,33,43,50,52,58,62]; chest pain in acute/sub-acute/chronic WAD [11,17,52,53]; postural changes [44,61] and reduced chest/thoracic mobility in CWAD [61]; thoracic outlet syndrome in CWAD [31,35,36,47,51]; involvement of the brachial plexus at all stages and across all levels of WAD severity [12,46,55,57,59]; muscle dysfunction in the form of the following: 1) heightened activity of the sternocleidomastoid during neck flexion [12,56], 2) delayed onset of serratus anterior during arm elevation at the chronic stage in mild WAD [45] and 3) a high prevalence of myofascial pain and trigger points in the scalene muscles [40,41], sternocleidomastoid [37,40,41] and mid/lower fibres of trapezius [16] within the subacute and chronic stages and across different levels of severity.…”
Section: Results Of Individual Studiesmentioning
confidence: 99%
“…There are limited and very variable findings of thoracic muscle dysfunction (activation) in WAD with studies investigating a relatively small number of muscles: sternocleidomastoid [12,49,56]; serratus anterior [45]; middle and lower fibres of trapezius [45,54]. Although it is difficult to derive meaningful conclusions with respect to serratus anterior and trapezius, there is evidence supporting changes in sternocleidomastoid muscle activation with heightened levels of activation during a task of cranio-cervical flexion; this increase in sternocleidomastoid activity however, was not seen during neck rotation [49].…”
Section: Controlmentioning
confidence: 99%